Legal analysis regarding certain time employment agreements in law number 6 of 2023 concerning employment creation - Alkhawi Noermatin (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
This research focuses on work agreements for a certain time in Law No. 11 of 2020 concerning work copyright, the difference in work agreements for a certain time in Law No. 13 of 2003 concerning Manpower and Law No. 11 of 2020 concerning Job Creation is very visible. seen more significantly in the rights received by contract workers. This research is expected to be able to answer the differences between Law No. 13 of 2003 concerning Manpower and Law Number 6 of 2023 concerning Job Creation. This research refers to Law No. 13 of 2003 and Law No. 6 of 2023 which is used as comparison material in this study. This research was written to answer several problems that occurred, namely regarding the subject 1. The length of time workers/workers have PKWT status 2. Whereas in Law Number 11 of 2020 concerning work copyright there is no probationary period. The method to be used in this research is the normative legal research method, namely research that prioritizes legal material in the form of legislation as a basic reference material in conducting research. From the results of the comparison of the 2 laws and regulations, it is hoped that they will be able to provide an explanation of legal products that can answer major issues, especially regarding workers' rights.